Reciprocity and incentive pay in the workplace - Robert Dur; Arjan Non; Hein Roelfsema (Institute for the Study of Labor (IZA), 2010)
We study optimal incentive contracts for workers who are reciprocal to management attention. When neither worker's effort nor manager's attention can be contracted, a double moral-hazard problem arises, implying that reciprocal workers should be given weak financial incentives. In a multiple-agent setting, this problem can be resolved using promotion incentives. We empirically examine these predictions using data from the German Socio-Economic Panel. We find that workers who are more reciprocal are significantly more likely to receive promotion incentives, while there is no such relation for individual bonus pay.
Keywords: D86; J41; M51; M52; M54; M55; 330; Reciprocity; social exchange; incentive contracts; double moral hazard; GSOEP; Anreizvertrag; Verantwortung; Moral Hazard; Deutschland